Analisis Pengendalian Kualitas Produk Cap Diameter 40 White Snap On Dengan Seven Tools - Muhammad Ajiwibowo Syawaludin; Ari Zaqi Al Faritsy (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
PT XYZ is a manufacturing company that produces bottle cap products such as flip top ∅40-12 white snap on, which in the production process in July and August 2022 there is a problem of the high number of reject products exceeding the regulatory limit, reaching 12.11% or 77,472 units from 640,00 units. The purpose of this study is to analyze the level of defects and find the highest factors that cause defects that occur in flip top ∅40-12 white snap on stamp products. Seven tools are methods that can be used to measure the level of defects and identify the cause of defects. The results of the analysis showed that the level of defects that occurred was not within the control limit and improvement was needed, because the proportion value moved irregularly past the UCL and LCL limits. From the analysis of the pareto diagram, the highest defect was obtained, namely black spots as many as 42,380 units with a percentage of 54.7%. Based on the fishbone diagram analysis, it was found that the causes of black spots were raw materials contaminated with dirt, selectors were not thorough and skilled, moulding was not in good condition, the use of sacks and work did not comply with SOPs, and a hot and dusty work environment. Keywords: Degree of Disability, Fishbone Diagram, Quality Control, Reject Product, Seven Tools